The role of microbiota and toll-like receptors in polycystic ovary syndrome: regulatory mechanisms of androgen metabolism - Xueming Huang; Liuyan Wu; Yunxiang Zhang; Xiaowen Lai; Dan Sun (Endocrine Connections, 2025)
Polycystic ovary syndrome (PCOS), a prevalent reproductive endocrine and metabolic disorder in gynecology, has hyperandrogenism (HA) as an essential pathophysiological alteration. PCOS patients, with or without HA, present diverse clinical manifestations. The function of intestinal or reproductive tract microorganisms in PCOS has drawn attention in recent years and is associated with the occurrence of HA. In this article, we review the connection between the microbial alterations in the intestinal and reproductive tracts and androgens in PCOS, and elaborate on the role of TLRs in this process.